2000
DOI: 10.2134/agronj2000.9261125x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Photoperiod on the Phenological Development of Barnyardgrass

Abstract: repeatedly demonstrated that knowledge of phenological development is critical in understanding crop growth,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 30 publications
9
42
2
1
Order By: Relevance
“…A rate change of -0.60 indicated that the effect of photoperiod was apparent from flowering to seed set. These results differed from green foxtail in which reproductive development after heading was found to be independent of photoperiod (Swanton et al 1999).…”
Section: Photoperiod Effectscontrasting
confidence: 91%
See 4 more Smart Citations
“…A rate change of -0.60 indicated that the effect of photoperiod was apparent from flowering to seed set. These results differed from green foxtail in which reproductive development after heading was found to be independent of photoperiod (Swanton et al 1999).…”
Section: Photoperiod Effectscontrasting
confidence: 91%
“…These parameters increased as photoperiod increased from 8 to 16 h. Influences of photoperiod on duration of reproductive development have also been reported in other dicotyledonous plants such as soy- Table 1 were expressed in terms of development rates (i.e., inverse of duration of development) and compared across phenological stages, we found no differences (P < 0.05) among photoperiod sensitivities (Table 2). This finding agrees with the observation in green foxtail (Swanton et al 1999) and barnyardgrass (Swanton et al 2000) but differs from that of Slafer and Rawson (1996). The latter authors suggested that photoperiod sensitivity varies with growth stage.…”
Section: Photoperiod Effectssupporting
confidence: 91%
See 3 more Smart Citations